The Risk Landscape within FinTech and InsurTech Business Models - Rupeika-Apoga, Ramona; Marano, Pierpaolo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The FinTech/InsurTech-based business models are gradually maturing and disrupting the offering and management of financial services (banking, financial and insurance) on the global stage. However, understanding of the risk landscape of the FinTech and InsurTech business models remains at an early stage due to the diverse nature of their activities and the rapid development of the field. Although FinTech and InsurTech offer the opportunity to accelerate economic growth and expand financial affordability/inclusion in all countries, they pose new risks to financial stability and integrity. This book contains five articles that offer a discussion of state-of-the-art developments or introduce new theoretical or practical advances in the identification, measurement and management of the risks arising from the FinTech/InsurTech-based business models.